Early estimates of seasonal influenza vaccine effectiveness in Europe among target groups for vaccination: results from the I-MOVE multicentre case-control study, 2011/12 - Kissling, E. (2012)
To provide an early estimate of 2011/12 influenza vaccine effectiveness (VE), we conducted a multicentre case–control study based on seven sentinel surveillance networks. We included influenza-like illness cases up to week 7/2012 from the vaccination target groups, swabbed less than eight days after symptom onset. Laboratory-confirmed influenza A(H3) cases were compared to negative controls. Adjusted VE was 43% (95% confidence interval: -0.4 to 67.7), suggesting low to moderate VE against influenza A(H3) in the early 2011/12 season.